A more critical role for silicon in the catalytic Staudinger amidation: silanes as non-innocent reductants. Issue 57 (24th May 2017) - Andrews, Keith G.; Denton, Ross M.
Abstract : We demonstrate that in situ -generated silyl ester intermediates are key mediators of the catalytic, traceless Staudinger amidation reaction. Abstract : A revised pathway for the catalytic Staudinger amidation reaction is presented that involves the intervention of in situ -generated silyl esters as the species responsible for amidation.